Research Status of Laser Surface Treatment of Cemented Carbide for Shield Cutter - WANG Qi, LONG Wei - min, MIAO Jin - qi, JIU Yong - tao (Cailiao Baohu)
Shield cutter is brazed by cemented carbide cutter head and high strength steel substrate. The premature falling off and the rapid wear of cemented carbide cutter head are the main reasons affecting the working life of shield cutter. Laser technology has unique advantages like energy saving, rapid processing, green manufacturing and precise automation. The reliability of shield cutter can be improved by laser surface treatment of cemented carbide. In this paper, laser treatment for improving cemented carbide properties was summarized, and its effect on improving shield cutter properties was discussed. Then, the improvement of brazing, surface friction and coating bonding strength of cemented carbide by laser texturing were reviewed in detail. Besides, the research progress of laser transformation hardening to treat cemented carbide surface and to improve wear resistance of cemented carbide tools was introduced. At last, the development trend of laser surface treatment of cemented carbide was briefly analyzed and prospected.